Selon en tant que marqueur d’altérité énonciative et ses traductions en polonais dans un corpus de presse - Dutka-Mańkowska, Anna (Neophilologica, 2008)
To describe Polish equivalents of the structure selon X, we admit that the above structure is the marker of enunciative alterity: a person who enunciates, presents content as taken up of another source. Presentation of discourse was analysed in press articles published in Le Monde Diplomatique and translated into Polish. Modal markers revealed further to the analysis of the corpus are more numerous than those indicated in dictionaries. In a series of tests we brought to view the characteristics of zdaniem, według, wedle and zgodnie z which were subsequently given the names found in the corpus and divided into classes. Ultimately, we discussed modifications in enunciations, related by correlation with obliteration of selon X in the translation.